The Influence of International Coffee Prices and Rupiah Exchange Rate on Export Volume of Coffee in Central Java - Nabila Alyssa Ramadhanty; Umar - Farouk; Suryadi - Poerbo (Politeknik Negeri Semarang, 2021)
The aim of this study is to determine the influence of the International Coffee Price and Rupiah Exchange Rate toward Volume of Central Java Coffee Exports in period 2015-2019. The data used in this research is quantitative data. This study use secondary data which obtained by collecting data from some sources which relevant to this study such as Badan Pusat Statistik (BPS), Bank Indonesia, International Coffee Organization and others. Regarding the data period, the data in this study use monthly data of International Coffee Price and Rupiah Exchange Rate toward Volume of Central Java Coffee Exports in period 2015-2019 with total 60 data. The study explored with multiple linier regression statistical analysis, along with descriptive analysis and classical assumption test namely normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, and linearity test. The results showed that partially international coffee prices had a negative and significant effect on the volume of coffee exports in Central Java and the rupiah exchange rate had a negative and insignificant effect on the volume of coffee exports in Central Java. Meanwhile, the international coffee price and the rupiah exchange rate simultaneously have a significant effect on the volume of coffee exports in Central Java.